POPULISM IN CONTEXT. A CROSS-COUNTRY INVESTIGATION OF THE FACEBOOK USAGE OF POPULIST APPEALS DURING THE 2019 EUROPEAN PARLIAMENT ELECTIONS - Bene, Márton; Magin, Empowerment; Haßler, Jörg; Russmann, Uta; Lilleker, Darren; Kruschinski, Simon; Jackson, Dan; Fenoll, Vicente; Farkas, Xénia; Baranowski, Paweł; Balaban, Delia (AoIR Selected Papers of Internet Research, 2023)
Recent scholarship demonstrated that Facebook is a convenient space for populist political communication as its unmediated and viral nature make populist appeals highly efficient in voters’ mobilization (Engesser et al., 2017). However, less attention has been paid to the way these populist messages appear on political actors’ communication, and what post- and page-level factors they are associated with. We investigate these questions in the context of the 2019 European Parliament (EP) election based on a unique cross-national dataset covering 12 European countries. In our research project we categorized more than 8,074 Facebook posts published on the main pages of 67 parties. Our findings show that the three dimensions of populist communication are used strategically different way and appear in different communication context. Anti-elitist messages are articulated in relation to economy, labor and social policy and immigration mostly by extreme parties. People-centrism is frequently used in relation to labor & social policy, and in European- and mobilization-focused posts all over the political landscape. Out-group messages appear in immigration-related posts and in far-right parties’ communication.